2008
DOI: 10.1037/0012-1649.44.4.1040
|View full text |Cite
|
Sign up to set email alerts
|

Development of cross-linguistic variation in speech and gesture: Motion events in English and Turkish.

Abstract: The way adults express manner and path components of a motion event varies across typologically different languages both in speech and cospeech gestures, showing that language specificity in event encoding influences gesture. The authors tracked when and how this multimodal cross-linguistic variation develops in children learning Turkish and English, 2 typologically distinct languages. They found that children learn to speak in language-specific ways from age 3 onward (i.e., English speakers used 1 clause and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
76
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 44 publications
15
76
1
1
Order By: Relevance
“…The finding that both French and English speaking children predominantly produce Path gestures are consistent with previous suggestions that children prefer 'separated' gestures, that is gestures that express either Path or Manner rather than conflating both (McNeill 2005;Özyürek et al 2008). The additional observation that English children show adjustments towards more conflation in later childhood is also consistent with previous studies.…”
Section: Speech and Gesture During Language Acquisitionsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding that both French and English speaking children predominantly produce Path gestures are consistent with previous suggestions that children prefer 'separated' gestures, that is gestures that express either Path or Manner rather than conflating both (McNeill 2005;Özyürek et al 2008). The additional observation that English children show adjustments towards more conflation in later childhood is also consistent with previous studies.…”
Section: Speech and Gesture During Language Acquisitionsupporting
confidence: 82%
“…Interestingly, in the domain of motion, two studies find evidence of gradual development towards adult-like gesturing in Spanish, Mandarin Chinese, English, and Turkish (McNeill 2005;Özyürek et al 2008). All children in these studies tend to produce more Manner and Path separately than adults who instead conflate Manner and Path in one gesture.…”
Section: Relating Gestures and Speech In Language Acquisitionmentioning
confidence: 99%
“…Future research may examine whether similar findings could be reported for other cultures and for other age groups. Recent studies (Gullberg 2009;Ö zyürek et al 2008) have already shown that the use of gesture to describe motion events is associated with the structure of the spoken language. Improvement of such investigations might greatly contribute to our understanding of how and when culture and language influence the development of gesture and speech.…”
Section: Resultsmentioning
confidence: 99%
“…The data used in this study were collected as part of a study investigating the cross-linguistic syntactic packaging of 'path' and 'manner' information in motion events (Allen, Özyürek, Kita, Brown, Furman, Ishizuka, & Fujii, 2007;Kita, et al, 2007;Özyürek, et al, 2001;Özyürek, Kita, Allen, Brown, Furman, & Ishizuka, 2008). The current study is a reanalysis of this existing data with a different research purpose-to investigate the way in which two-handed gesture varies with age.…”
Section: Datamentioning
confidence: 99%